Interactions among environment, achivement, behaviour and personal attributes of Malaysian secondary school boys : a structural equation modeling study - Jamilah Jaafar (Institute of Education, International Islamic University Malaysia, 2012)
While most efforts related to gender equity in education focus on improving girls' access to quality education, boys' underachievement in education is a matter of urgent concern. In Malaysia, for example, boys are lagging behind their female counterparts in national examinations, enrollment in higher education and all other positive outcomes of schooling. Using Urie Bronfenbrem1er's Ecological System Theory and Albert Bandura' s Social Cognitive Theories, this study investigates factors affecting boys' academic achievement, personality attributes and behaviour. It specifically examines how environmental actors (namely parental support, teacher .effectiveness and peer relationships) contributed to boys' academic achievement through influencing their risk-taking behaviours and positive behaviours in school (school engagement) as well as their religiosity and masculinity. The study employs both qualitative and quantitative methods of data collection. In the qualitative phase, which involved focus-group interviews as well as in-depth interviews with students and teachers in selected schools, seven themes emerged related to the factors influencing boys' development. Based on the qualitative findings, an instrument was constructed and validated for use in the final quantitative study. In the final quantitative study, clustered stratified sampling was employed to select a sample of 1844 boys from secondary schools from various states in Peninsular Malaysia. Structural Equation Modeling was employed for Confirmatory Factor Analysis (CF A) and for testing the Structural Model to identify direct and reciprocal relationships. The findings revealed that environment has strong effects on religiosity and positive behaviour in school, moderate effects on masculinity and achievement, and negative moderate effects on risky behaviour. Positive behaviour, masculinity and religiosity weakly effect achievement. The findings also revealed that religiosity has moderate effects on masculinity and positive behaviour, and negatively affected risky behaviour. Masculinity hardly affected positive behaviour, risky behaviour, religiosity and achievement. The findings supported all the hypotheses. In the reciprocal model, environment and personal attributes strongly affect behaviour. In view of these finding, the study suggests that developmental problems and boys' achievement in schools should be approached from more comprehensive perspectives that observe the greater portion of the dynamics involved in boy education. The research concludes by offering several recommendations to policy makers, teacher, parents and future researchers.